Causal factors in primary open angle glaucoma: a phenome-wide Mendelian randomisation study - Thomas H. Julian; Zain Girach; Eleanor Sanderson; Hui Guo; Jonathan Yu; Johnathan Cooper-Knock; Graeme C. Black; Panagiotis I. Sergouniotis (Scientific Reports, 2023)
Abstract Primary open angle glaucoma (POAG) is a chronic, adult-onset optic neuropathy associated with characteristic optic disc and/or visual field changes. With a view to identifying modifiable risk factors for this common neurodegenerative condition, we performed a ‘phenome-wide’ univariable Mendelian randomisation (MR) study that involved analysing the relationship between 9661 traits and POAG. Utilised analytical approaches included weighted mode based estimation, the weighted median method, the MR Egger method and the inverse variance weighted (IVW) approach. Eleven traits related to POAG risk were identified including: serum levels of the angiopoietin-1 receptor (OR [odds ratio] = 1.11, IVW p = 2.34E-06) and the cadherin 5 protein (OR = 1.06, IVW p = 1.31E-06); intraocular pressure (OR = 2.46–3.79, IVW p = 8.94E-44–3.00E-27); diabetes (OR = 5.17, beta = 1.64, IVW p = 9.68E-04); and waist circumference (OR = 0.79, IVW p = 1.66E-05). Future research focussing on the effects of adiposity, cadherin 5 and angiopoietin-1 receptor on POAG development and progression is expected to provide key insights that might inform the provision of lifestyle modification advice and/or the development of novel therapies.